Algoritma Extended Weighted Tree Similarity untuk Memberikan Solusi Memasak pada J2ME - Yosephine, Halim; Ramos, Somya; Charitas, Fibriani (Universitas Sam Ratulangi, 2012)
Abstract The aim of this thesis is to give the simplicity in cooking with limited ingredients for the users by using mobile technology (J2ME). The aim of this thesis can be done by using Extended Weighted Tree Similarity Algorithm, a calculation to find out the highest weight similarity between the menu which has been inputted in the application as a database; and the inputted ingredients from the users of this application. The conclusion of this thesis is that Algorithm Extended Weighted Tree Similarity can be implemented into mobile technology (J2ME). Keywords: extended weighted tree similarity, cooking smart, J2ME Abstrak Tujuan dari penelit ian ini adalah memberikan kemudahan dalam memasak dengan bahan yang terbatas bagi pengguna dengan menggunakan teknologi mobile (J2ME). Tujuan dari tesis ini dapat dilakukan dengan menggunakan Algoritma Extended Weighted Tree Similarity, perhitungan untuk mengetahui kesamaan bobot tertinggi antara menu yang telah diinput dalam aplikasi sebagai database, dan bahan-bahan dimasukkan dari pengguna aplikasi ini. Kesimpulan dari tesis ini adalah bahwa Algoritma Extended Weighted Tree Similarity dapat diimplementasikan ke dalam teknologi mobile (J2ME). Kata Kunci : extended weighted tree similarity, cooking smart, J2ME